How to Get the Full Prism Effect. (21st August 2015) - Pochopien, Klaudia; Fahle, Manfred
We investigate how the immediate correction effect decreases mispointing under prisms. Subjects performed rhythmic pointing movements under different conditions with horizontally shifting prisms. Even the first (initial) pointing error is much smaller than the prismatic shift, a phenomenon called the immediate correction effect. Knowledge about the structure of the room and of objects in the room obtained before the prisms were worn may limit the amount of the prismatic displacement perceived. We therefore compared the direct prism effect as well as prismatic adaptation with room illumination switched on versus switched off. Our 44 subjects participated in two experiments, with varying amounts of information about room structure available. The results show a direct effect corresponding to the optical power of the prisms in the dark condition, when in addition body position was slightly rotated in direction of the prismatic shift. But even in the dark, a significant immediate correction effect arises with the fixed body position. The largest immediate correction amounting to almost half of optical displacement arose in the standard condition of bright light and fixed body position.